Regards croisés sur les feuilles de route hydrogène de trois pays : le Canada, le Japon et la France. Quels enseignements ? - Laurent Jammes (VertigO)
The multiple uses of hydrogen – as a mean to store energy, for mobility or cogeneration of electricity and heat, as a vector to bridge between energy networks – make it a key vector of the energy transition. Many countries and regions are thus embarking on a hydrogen roadmap, with the objective of a progressive decarbonization of their energy system. The analysis of hydrogen technologies deployment trajectories – in Canada, Japan and France – shows that the success of these initiatives depends on several sets of conditions : 1) a clear and well-argued contribution to the energy transition effort, associated with strong political support ; 2) national R&D, demonstration and industrialization activities, preparing for deployment, and supported by appropriate financial mechanisms ; 3) engagement of all stakeholders in the debates on the role of hydrogen in the energy transition, as well as in the definition and implementation of local deployment project